Intramuscular circulation of the lumbar multifidus in different trunk positions on sitting - Sato, Naritoshi; Watanabe, Kei; Kitamura, Takuya; Suzuki, Yusuke; Kubo, Masayoshi; Kanda, Masaru (Journal of Spine Research, 2020)
A deficiency in lumbar muscle blood circulation is considered to be a major risk factor for nonspecific low back pain. The aim of this study was to investigate changes in relative circulation over time in the lumbar multifidus in different positions on sitting.Twelve healthy subjects (7 males, 5 females, average age: 20.9 years) without low back pain for the past twelve months were recruited. They received a full explanation and all agreed to participate in this study. Near-infrared spectroscopy (NIRS) was used to non-invasively measure total hemoglobin (Total-Hb) and oxygenated hemoglobin (Oxy-Hb) in the lumbar multifidus at the L5-S1 segment. All measurements were obtained in a neutral position, 60-degree trunk-flexed position, and 20-degree trunk-extended position on sitting. Subjects were asked to move into either a flexed or an extended position from the starting (neutral) position in 3 seconds, timed by a metronome, and to maintain these positions for 30 seconds. The angles of flexed and extended positions were measured with a goniometer, and self-made devices were used to properly maintain these positions. All participants received education and practice time in order to be able to adapt proper body movements and positions prior to assessment. The measurements of Total-Hb and Oxy-Hb were compared at -3 (neutral position), 0, 10, 20, and 30 seconds in each flexed and extended position on sitting.In flexion, Total-Hb and Oxy-Hb of the lumbar multifidus were significantly decreased from a neutral (-3 seconds) to flexed (0 second) position (Total-Hb: p=0.002, Oxy-Hb: p=0.004); however, there were no significant differences in the flexed position. In extension, Total-Hb and Oxy-Hb of the lumbar multifidus were significantly increased from 0 to 10 seconds (Total-Hb: p<0.001, Oxy-Hb: p<0.001); however, there were no significant differences from the neutral (-3 seconds) to extended (0 second) position, or from 10 to 30 seconds.The results of this study indicate that the intramuscular circulation of the lumbar multifidus decreases immediately once the trunk starts moving into a flexed position on sitting. On the other hand, the intramuscular circulation of the lumbar multifidus increases for up to 10 seconds once the trunk starts moving into an extended position. Therefore, it might be more beneficial for a person to avoid a flexed position and move into an extended position for therapeutic exercise in order to increase blood circulation of the lumbar multifidus on sitting.